Angiopoietin-2 Immunohistochemical Expression in Oral Squamous cell Carcinoma - Intisar A Al Sarraf; Ban F. Al Drobie (College of Dentistry/ University of Baghdad, 2019)
Background: There are various secreted proteins affecting the prognosis of oral squamous cell carcinoma (OSCC) and one of them is Angiopoietin-2(Ang-2) which is thought to have an essential role in the development and progression of the tumor. Aim of the study: This study was conducted to determine the expression of (Ang-2) in (OSCC) to assess its correlations with clinicopathological parameters of the tumor. Material and Methods: 36 formalin- fixed, paraffin- embedded tissue blocks histologically diagnosed as OSCC were examined for Ang-2 immunohistochemical expression semi quantitively. Results: The expression of Ang-2 was significantly associated with histopathological grade (P value=0.023), while there is no significant association with the clinical parameters analyzed in OSCC patients. Conclusion: A significant association between Ang-2 expression and histopathological grade of OSCC may predict its biological behavior.